Improving Students' Conceptual Understanding by Implementing the Project Based Learning Model in Islamic Education Learning at SD Negeri 13 Kuala Batee - Salmi; Samsimar B (Journal of Action Research in Islamic Education, 2025)
This study aims to improve students’ conceptual understanding through the implementation of the Project Based Learning (PjBL) model in Islamic Education learning at SD Negeri 13 Kuala Batee. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 28 fifth-grade students. Data were collected through conceptual understanding tests, observation sheets, and field notes. Quantitative data were analyzed using descriptive statistics to measure improvement across cycles, while qualitative data were analyzed through interactive analysis techniques to support the interpretation of findings. The results indicate a significant improvement in students’ conceptual understanding after the implementation of the PjBL model. The mean pre-cycle score was 62.14, with only 39.29% of students achieving the minimum mastery criterion (MMC). After Cycle I, the mean score increased to 74.86, with 67.86% of students meeting the MMC. In Cycle II, the mean score further improved to 84.21, and 89.29% of students achieved mastery. The normalized gain (N-gain) score of 0.61 indicates a moderate-to-high improvement category. Observational data also revealed increased student engagement, collaboration, and critical thinking skills during project activities. These findings demonstrate that the Project Based Learning model effectively enhances students’ conceptual understanding in Islamic Education by fostering active participation, contextual learning, and collaborative inquiry. The study contributes to the growing body of empirical evidence supporting innovative pedagogical approaches in Islamic Education at the elementary level and provides practical implications for teachers seeking to strengthen conceptual learning outcomes through student-centered strategies.